A Phase Transformation‐Resistant Electrode Enabled by a MnO2‐Confined Effect for Enhanced Energy Storage. (6th May 2019) - Guo, Wei; Yu, Chang; Li, Shaofeng; Song, Xuedan; Yang, Ying; Qiu, Bo; Zhao, Changtai; Huang, Huawei; Yang, Juan; Han, Xiaotong; Li, Dan; Qiu, Jieshan
Abstract: Although the transition metal oxides/hydroxides are regarded as highly promising and attractive materials for efficient energy storage, a precycling/activation process is usually adopted to stabilize phase components and achieve reversible output. Moreover, the intrinsic mechanism involved in precycling process is not always concerned and remains to be further decoupled. Herein, overcoming the challenges associated with the MnO2 ‐confined effect is proposed, which is enabled by in situ dissolving‐out and conversion of Mn species in MnO2 derived from the Co‐induced effect. Notably, a high electrochemical stability without activation and a superior initial Coulombic efficiency of 96.2% can be achieved without any precycling or activation process, which increases by 33.5% in comparison to the efficiency of the hybrids without MnO2 surface‐confined effect. And a specific capacity up to 164 mAh g −1 at 2 A g −1 can be achieved with an excellent capacity retention rate of 90% at 30 A g −1, which only drops slightly and remains at a high level of 87% even after 5000 cycles. This strategy may function as a model for the design and configuration of highly stable electrodes toward high‐efficient energy storage and conversion applications. Abstract : A phase transformation‐resistant electrode confined by MnO2 is presented. This device enables fast responsive charge storage, superior electrochemical stability, and a super‐high initial Coulombic efficiency of 96.2% with a stable energy output, which is superior to that of its counterpart.